Digital Camp for Student : Workshop Pemrograman Java untuk Siswa SMK Negeri Air Joman Jurusan Rekayasa Perangkat Lunak - Rolly Yesputra; Edi Kurniawan; Nasrun Marpaung; Nuriadi Manurung (Smart Education, 2021)
Abstract: The 4.0 Industrial Revolution can be seen directly from the very rapid progress and changes in information technology in various fields. To be able to keep up with technological developments in the era of the Industrial Revolution 4.0, SMK students must be able to follow the development of information technology, especially programming. With the motto